2013
DOI: 10.1021/es304332v
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Elimination by a Top Predator, Esox lucius

Abstract: Top-level piscivores are highly sought after for consumption in freshwater fisheries, yet these species contain the highest levels of the neurotoxin monomethylmercury (MMHg) and therefore present the greatest concern for MMHg exposure to humans. The slow elimination of MMHg is one factor that contributes to high levels of this contaminant in fish; however, little quantitative information exists on elimination rates by top predators in nature. We determined rates of MMHg elimination in northern pike (Esox luciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Both laboratory and manipulative field studies have demonstrated that fish eliminate MeHg very slowly [41,42,43]. For example, Van Walleghen and colleagues [43] monitored Hg(II) in northern pike, which had naturally accumulated isotope-enriched MeHg through a whole-lake loading study, after their transfer to a different lake.…”
Section: Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Both laboratory and manipulative field studies have demonstrated that fish eliminate MeHg very slowly [41,42,43]. For example, Van Walleghen and colleagues [43] monitored Hg(II) in northern pike, which had naturally accumulated isotope-enriched MeHg through a whole-lake loading study, after their transfer to a different lake.…”
Section: Fishmentioning
confidence: 99%
“…For example, Van Walleghen and colleagues [43] monitored Hg(II) in northern pike, which had naturally accumulated isotope-enriched MeHg through a whole-lake loading study, after their transfer to a different lake. Spiked Hg(II) was detected in muscle samples over the course of the 7-year study, and the authors estimated the half-life of Hg(II) in muscle at 3.3 years.…”
Section: Fishmentioning
confidence: 99%
“…Although the rate at which fish eliminate Hg from their bodies is slow, Hg-elimination rates are measurable [4143]. In contrast, long-term decreases in the PCB body burden of fish are undetectable.…”
Section: Sex Difference In Pcb Concentrations Versus Sex Difference Imentioning
confidence: 99%
“…In addition, the rates of Hg elimination by fish may be slower than those portrayed in the Hg elimination submodel based on recent research. Results from a set of whole-lake manipulation experiments involving isotopically enriched Hg suggested that the Hg elimination submodel overestimated Hg-elimination rates for yellow perch and northern pike by 49 to 209 %, depending on whether the chronic exposure form or the acute exposure form of the Hg elimination submodel was used [42, 43]. In sum, the Hg mass balance models may need further refinement to account for species-specific Hg-elimination rates.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Based on these incidents, the symptoms of MeHg poisoning were elucidated and include ataxia, dysarthria, tremor, narrowing of the visual field (including blindness), and, in severe cases, death (1, 7,19,20). In the aftermath of these events, the toxicokinetics of MeHg were examined, and it was found that MeHg is efficiently absorbed (41) but slowly excreted (28), leading to in vivo half-lives of 2 to 3 months in humans (7, 40). Additionally, 10% of the body burden of MeHg is in the brain (12), where MeHg is demethylated to inorganic mercury (28).…”
mentioning
confidence: 99%